Refrigerated Warehouse Operation Under Real Time Pricing - Stoeckle, Ronald (University of Wisconsin-Madison, 2000)
Refrigerated warehouses play an essential role in the food delivery chain. The construction and operation of refrigerated storage is growing. Because of the relatively high energy intensity associated with the operation cold storage warehouses, controlling energy consumption and the cost of energy is often an important operational concern. Under standard electricity rates, refrigerated warehouses are usually operated continuously to keep the products in storage at a constant temperature. Deregulation of the electricity markets over the past years has lead to new electricity pricing approaches, one of which is called real-time pricing (RTP). Under real-time pricing, the electricity price varies hourly. The hourly changing electricity price offers the possibility of cost savings for the customer if demand can be reduced during hours of high prices and shifted to hours of lower prices. This study investigates the possibility to utilize product stored in a refrigerated warehouse as a thermal energy storage media to minimize energy costs under real-time pricing rate structures. Demand shifting, i.e. precooling the warehouse during hours of low electricity prices to a lower temperature and shutting down the refrigeration equipment during high price hours, can yield operating cost savings. The increase in product temperature during equipment shutdown limits the possible floating duration. A computer model of a representative refrigerated warehouse was developed. The model includes the building envelope, the refrigeration systems and a model of the stored product. A thermally massive and a lightweight wall construction were investigated. From the results of the simulation runs, a method was developed that allows determining if demand shifting on the next day is likely to offer operating cost savings. The method includes forecasting the allowable floating duration based on the outside air temperatures for the next day and deciding on the best shutdown period. A simple criterion based on a price ratio was found to be a good indicator if demand shifting offers savings. The simulation results indicate that operating cost savings through demand shifting are relatively small compared to the yearly operating cost. Installation of additional refrigeration capacity results in projected savings of about 7-11 % of the yearly electricity cost. Considerably increased energy demand during the precooling period is the reason for the small projected savings. Only high real-time peak prices can compensate for the cost penalty paid during precooling.
Under the supervision of Professors Douglas Reindl and John Mitchell; 216pp.
Keywords: Thesis (M.S.)--University of Wisconsin--Madison, 2000.; Dissertations Academic Mechanical Engineering.; University of Wisconsin--Madison. College of Engineering.